Bile resistance and bile salt deconjugation activity of Bifidobacterium pseudocatenulatum G4 in a simulated colonic pH. - Rasti, Babak; Mustafa, Shuhaimi; Meor Hussin, Anis Shobirin; Nateghi, Leila; Meimandipour, Amir; Abd. Manap, Mohd. Yazid (WFL Publisher, 2011)
The ability of Bifidobacterium pseudocatenulatum G4 to survive and tolerate bile acids exposure and its bile salt hydrolase activity was investigated. The growth rate of B. pseudocatenulatum G4 (106, 108 and 1010cfu/ml) decreased in the presence of 2.0% oxgall compared to the control (without oxgall), however, the colonic concentration of bile acids (0.1%) did not show any significant effect (p<0.05) on the growth rate of this strain in three different simulated colonic pH (5.7, 6.2 and 6.8). Bile salt hydrolase activity, which is the measurement of enzyme activity responsible for bile salt deconjugation, was quantified by high pressure liquid chromatography (HPLC) assay. B. pseudocatenulatum G4 demonstrated high deconjugation rate (82 to 100%) in TPY broth supplemented with 0.25 mM and 5.0 mM of all six different types of bile acids including: taurocholic acid (TCA), glycocholic acid (GCA), taurochenodeoxycholic acid (TCDCA), glycochenodeoxycholic (GCDCA), taurodeoxycholic acid (TDCA) and glycodeoxycholic acid (GDCA). Overall, the percentage of deconjugation activity was higher in TPY medium supplemented with 0.25 mM bile acids compared to TPY broth with 5.0 mM bile acids. Also, B. pseudocatenulatum G4 showed good tolerance to bile acids. Generally, B. pseudocatenulatumG4 deconjugated glycoconjugated bile acids in higher amount compared to tauroconjugate ones. Bifidobacterium pseudocatenulatum G4 demonstrated good tolerance of bile acids suggesting that it would be capable of surviving in the colon and deconjugating bile salts if used as a probiotic.